How basic public health services shape social integration: Evidence from domestic migrants in China - Jiahao Zhao; Xinyi Zhu; Zhisen Gu; Sining Zheng; Zixiao Jiang (PLoS ONE, 2026)
The demand for and awareness of utilizing resident health services are increasing, yet uneven development across regions has led to uneven population mobility. Against this backdrop, as a crucial safeguard for the healthy lives of the mobile population, basic public health services profoundly influence the quality of life and development opportunities of these populations in urban settings. To elucidate the impact of basic public health services on the social integration of the urban mobile population, this study utilizes data from the China Migrants Dynamic Survey and employs empirical analysis to investigate the multidimensional effects of basic public health services on the social integration of domestic migrants. According to the results of the study, (1) basic public health services contribute to enhancing the social integration of domestic migrant population. This conclusion remains valid after robustness checks, with self-assessment of health playing a mediating role, and (2) the impact of basic public health services on the social integration of the domestic migrant population varies across different urban groups. This study contributes to examining and clarifying the policy effects of basic public health services in promoting the social integration of domestic migrants, providing empirical evidence for using basic public health services as a key lever to facilitate the social integration of domestic migrants.